Environmental Education in Non-conventional Spaces of Education Managed by Bogota Environment Offices: Advance of a State of Art (2016)
This communication is part of the first phase of an investigation project of the doctorate in education at the University Francisco José de Caldas, about the state-of-the-art advance in the search of stablishing a background and justification elements about the identified problems. This project inquires about how environmental education is assumed and implemented in non-conventional  spaces of education, managed by Bogotá environment offices (Botanical garden and the Secretary of the environment) and in the state of-the-art we ask the question What do we know about the object of study? setting up an advance from a stablished route in the line of investigation “Incorporation of environmental dimension in science education at doctorate”. This project is not only conceived from a recent and not very explored base of investigation, but also allows us to conceive the reflection from a more specific context like the entities involved in such topic, being responsible of leading policies, administration and environmental education in Bogotá. This project will also intend to stablish relations between how to assume and implement environmental education in formal and non-formal ambit and the possible emergence of environmental didactics for such spaces.